PERAMALAN TINGKAT PENGHUNIAN KAMAR DENGAN MEMANFAATKAN DATA GOOGLE TRENDS DI PROVINSI BANTEN - Muhammad Fajar; Teuku M. Madinah; Hendro Prayitno (LPPM Universitas Bina Bangsa, 2021)
The purpose of this paper is to forecast the room occupancy rate (ROR) of star hotels by utilizing Google Trends data, in addition to historical ROR data. The data used is the ROR (%) which comes from the Badan Pusat Statistik-Statistics Indonesia and the Google Trends query index using the search word